Design and measurement of the receiving antenna for electromagnetic field energy harvesting in UHF band - Fahmy Rinanda Saputri; Sunarno Sunarno; Singgih Hawibowo (Institute of Advanced Engineering and Science, 2023)
This paper aims to design a receiving antenna for harvesting energy using the wireless energy transfer method based on the ultra-high frequency (UHF) band. The study was conducted by comparing four types of the receiving antenna design. A mathematical and experimental analysis has been done to evaluate the performance of the designed antennas. A Yagi-Uda antenna is utilized as the transmitter. The results show that the zig-zag type antenna has the best performance. It can receive electromagnetic energy from a transmitter with maximum efficiency is 0.1% for the receiving antenna volume of 0.34 cm3. The proposed method can meet the energy necessity of an implant device with a charging time of approximately 21.61 hours for the 700 mAh rechargeable battery capacity. As our preliminary conclusion, based on our results, this proposed method can be used as a reference for the practice in the WET field and the medical and restricted areas in the electromagnetic energy harvesting case.